Implementation of Fuzzy Logic on Internet of Things-Based Greenhouse - Yosep, Stanislaus (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
This research is an internet of things-based monitoring system using LoRaWAN and the IoT Thingspeak application server. This research is focused on helping farmers, or the agriculture sector focused on Pakcoy. Pakcoy is a plant that can live at an altitude of 500-1200 meters above sea level using the Greenhouse concept; Pakcoy plants can be protected from pests. Nutrients for Pakcoy are sprayed through the leaves, accelerating the provision of nutrients for plants. The Fuzzy Sugeno method is used to control the Greenhouse temperature and Soil Moisture for effective plant development, as well as monitoring the Greenhouse temperature, soil moisture, and pH of the growing media based on the Internet of Things that uses the Long Range 915 Mhz, therefore, the users can find out in real-time the data can be accessed by using Thingspeak and can be used in areas where internet access is difficult.